Failing forward [turning mistakes into stepping-stones for success] - Maxwell, John C., 1947- (Nashville, TN : Nelson Business, 2004)
Beginning with the premise that the major difference between achieving people and average people is their perception of and response to failure, the author takes a close look at failure and reveals that the secret to moving beyond failure is to learn from it and use it as a stepping-stone.
Subtitle from container.
Abridged.
Compact disc.
Read by the author.
Keywords: Success -- Psychological aspects; Self-actualization (Psychology) -- Case studies; Success in business -- Case studies; Failure (Psychology)